Extracellular vesicles in anti-tumor drug resistance: Mechanisms and therapeutic prospects - Hao-Yang Cheng; Guang-Liang Su; Yu-Xuan Wu; Gang Chen; Zi-Li Yu (Elsevier, 2024)
Drug resistance presents a significant challenge to achieving positive clinical outcomes in anti-tumor therapy. Prior research has illuminated reasons behind drug resistance, including increased drug efflux, alterations in drug targets, and abnormal activation of oncogenic pathways. However, there's a need for deeper investigation into the impact of drug-resistant cells on parental tumor cells and intricate crosstalk between tumor cells and the malignant tumor microenvironment (TME). Recent studies on extracellular vesicles (EVs) have provided valuable insights. EVs are membrane-bound particles secreted by all cells, mediating cell-to-cell communication. They contain functional cargoes like DNA, RNA, lipids, proteins, and metabolites from mother cells, delivered to other cells. Notably, EVs are increasingly recognized as regulators in the resistance to anti-cancer drugs. This review aims to summarize the mechanisms of EV-mediated anti-tumor drug resistance, covering therapeutic approaches like chemotherapy, targeted therapy, immunotherapy and even radiotherapy. Detecting EV-based biomarkers to predict drug resistance assists in bypassing anti-tumor drug resistance. Additionally, targeted inhibition of EV biogenesis and secretion emerges as a promising approach to counter drug resistance. We highlight the importance of conducting in-depth mechanistic research on EVs, their cargoes, and functional approaches specifically focusing on EV subpopulations. These efforts will significantly advance the development of strategies to overcome drug resistance in anti-tumor therapy.